Michael Polanyi's Daring Epistemology and the Hunger for teleology - Gelwick, Richard (Zygon, 2005)
Abstract. The linking of Michael Polanyi's name with a center (now changed to another name) at Baylor University that espoused intelligent-design theory calls for examination of Polanyi's teleology. This examination attempts to put Polanyi's epistemology in the perspective of his total philosophical work by looking at the clarification of teleology in philosophy of biology and in the framework of three major features of Polanyi's thought: open and truth-oriented, purposive but open to truth, and transcendent yet intelligible. The conclusion is that Polanyi would not support intelligent design according to the nature of his own theory.